2011
DOI: 10.1007/s10926-011-9300-x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Rehabilitation in Twenty-First Century Asia Pacific: Facilitating Health and Work: An Introduction

Abstract: Introduction Asia Pacific has more than 20 countries which are different in terms of size, population, gross domestic product (GDP), and technological development. This paper highlights certain common obstacles faced by the workers' compensation and occupational rehabilitation systems in the region. Methods A review was conducted of the 9 papers contained in this supplementary issue of the Journal of Occupational Rehabilitation. Important items discussed in each paper were extracted and collated. The suggestio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…This could be a potential model of care for injured workers in Asian countries where work injury management policies are not yet established. Future implementation of the RTWC model of care will need to consider overcoming the current obstacles and development of an occupational rehabilitation and work injury management framework for successful RTW [9,10,28,42,43,44].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be a potential model of care for injured workers in Asian countries where work injury management policies are not yet established. Future implementation of the RTWC model of care will need to consider overcoming the current obstacles and development of an occupational rehabilitation and work injury management framework for successful RTW [9,10,28,42,43,44].…”
Section: Resultsmentioning
confidence: 99%
“…Results from this research study show that the RTWC model can be a promising model of care to be implemented in Singapore, and also likely in Asian countries where work injury management policies are still absent. In the article "Occupational rehabilitation in twenty-first century Asia Pacific: Facilitating health and work" [28], the authors identified the common obstacles in the provision of occupational rehabilitation services in the Asia Pacific countries: (i) Legislation and policy awareness of stakeholders, (ii) Coordination and synergy of services, and (iii) Competence building of professionals.…”
Section: Overcoming Obstacles In Provision Of Occupational Rehabilitamentioning
confidence: 99%
“…[3][4][5] İş engelliliği ise işçinin çalışma gücünün belli miktarda veya tam kaybına, gelir kaybına, yüksek tıbbi maliyetlere, psikolojik iyilik hâlinin veya mesleki ilişkilerinin bozulmasına neden olan durumdur. 6 İş kaynaklı engellilik, hem gelişmekte olan hem de gelişmiş ülkelere büyük bir yük getirmektedir. Dünya çapında her yıl iş kazaları veya meslek hastalıkları sonucu 2 milyon erkek ve kadın ölmekte, 90 milyon "disability adjusted life years (DALY)" yükü oluşturmakta ve 268 milyon ölümcül olmayan iş yeri kazası sonucu oluşan engellilik işten çıkarmayla sonuçlanmaktadır.…”
unclassified